2010
DOI: 10.3996/102009-jfwm-013
|View full text |Cite
|
Sign up to set email alerts
|

Population Demographics and Dynamics of Colonizing Elk in a Desert Grassland–Scrubland

Abstract: Elk Cervus elaphus are rare in Southwestern desert grassland and desert-scrub habitats, and these habitats are anecdotally considered unsuitable for elk. We studied a colonizing herd in a Southwestern desert grassland-scrubland in northwestern New Mexico to determine the condition and population dynamics of elk in this habitat type. We radiotracked # 24 adult (1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…By calculating λ , we were able to compare our results with other studies. Bender and Piasecke () reflected a high maximum estimate of λ for 3 consecutive years as 1.22, 1.22, and 1.08, which were comparable to the Bender et al (), who recorded λ = 1.22 for the fastest growing elk herd ever documented. We believe our estimate of λ = 1.19 mostly indicates the population is productive and growing.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…By calculating λ , we were able to compare our results with other studies. Bender and Piasecke () reflected a high maximum estimate of λ for 3 consecutive years as 1.22, 1.22, and 1.08, which were comparable to the Bender et al (), who recorded λ = 1.22 for the fastest growing elk herd ever documented. We believe our estimate of λ = 1.19 mostly indicates the population is productive and growing.…”
Section: Discussionsupporting
confidence: 67%
“…Calf:female ratios are practical indices of herd productivity (Gaillard et al , Bender and Piasecke ). Collection of calf:female ratio data before post‐weaning mortality and calf recruitment into the adult population gave us the maximum potential finite rate‐of‐increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nelson and Burnell (1975) reported that stands with the densest canopy cover received the greatest amount of summer use and Marcum (1975) reported that elk selected summer bed sites in areas with the greatest canopy cover. However, Cook et al (1998) did not find that summer thermal cover decreased energy requirements, and other studies exhibited that elk populations could successfully inhabit areas with little or no tree overstory during summer (McCorquodale 1991, Merrill 1991, Strohmeyer and Peek 1996, Bender and Piasecke 2010. Though reasons why are unclear, during our study, elk typically selected areas with greater canopy cover.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of elk resource selection have been conducted in mountainous terrain (Ager et al , McCorquodale , Webb et al , Beck et al ). However, elk have been expanding into many landscapes where they have not occurred in recent times, such as cultivated areas and non‐forested, semiarid environments (McCorquodale et al , McCorquodale , deCalesta and Witmer , Sawyer et al , Bender and Piasecke ). To the best of our knowledge, this study is the first to investigate resource use by non‐migratory elk within a semiarid riparian corridor.…”
mentioning
confidence: 99%